Report of the preparatory committee for the new international development strategy volume II - United Nations (New York : United Nations, 1979)
This publication is a report on the Preparatory committee for the new international development strategy held at the United Nations Headquarters from 11 to 22 June 1979.
lje 04/05/17
Loans
Keywords: Economic development